/- Copyright (c) 2014 Floris van Doorn. All rights reserved. Released under Apache 2.0 license as described in the file LICENSE. Authors: Floris van Doorn, Leonardo de Moura, Jeremy Avigad The order relation on the natural numbers. -/ import data.nat.basic algebra.ordered_ring open eq.ops namespace nat /- lt and le -/ theorem le_of_lt_or_eq {m n : ℕ} (H : m < n ∨ m = n) : m ≤ n := or.elim H (take H1, le_of_lt H1) (take H1, H1 ▸ !le.refl) theorem lt_or_eq_of_le {m n : ℕ} (H : m ≤ n) : m < n ∨ m = n := lt.by_cases (suppose m < n, or.inl this) (suppose m = n, or.inr this) (suppose m > n, absurd (lt_of_le_of_lt H this) !lt.irrefl) theorem le_iff_lt_or_eq (m n : ℕ) : m ≤ n ↔ m < n ∨ m = n := iff.intro lt_or_eq_of_le le_of_lt_or_eq theorem lt_of_le_and_ne {m n : ℕ} (H1 : m ≤ n) (H2 : m ≠ n) : m < n := or.elim (lt_or_eq_of_le H1) (suppose m < n, this) (suppose m = n, by contradiction) theorem lt_iff_le_and_ne (m n : ℕ) : m < n ↔ m ≤ n ∧ m ≠ n := iff.intro (suppose m < n, and.intro (le_of_lt this) (take H1, lt.irrefl _ (H1 ▸ this))) (suppose m ≤ n ∧ m ≠ n, lt_of_le_and_ne (and.elim_left this) (and.elim_right this)) theorem le_add_right (n k : ℕ) : n ≤ n + k := nat.induction_on k (calc n ≤ n : le.refl n ... = n + zero : add_zero) (λ k (ih : n ≤ n + k), calc n ≤ succ (n + k) : le_succ_of_le ih ... = n + succ k : add_succ) theorem le_add_left (n m : ℕ): n ≤ m + n := !add.comm ▸ !le_add_right theorem le.intro {n m k : ℕ} (h : n + k = m) : n ≤ m := h ▸ le_add_right n k theorem le.elim {n m : ℕ} (h : n ≤ m) : ∃k, n + k = m := by induction h with m h ih;existsi 0; reflexivity; cases ih with k H; existsi succ k; exact congr_arg succ H theorem le.total {m n : ℕ} : m ≤ n ∨ n ≤ m := lt.by_cases (suppose m < n, or.inl (le_of_lt this)) (suppose m = n, or.inl (by subst m)) (suppose m > n, or.inr (le_of_lt this)) /- addition -/ theorem add_le_add_left {n m : ℕ} (H : n ≤ m) (k : ℕ) : k + n ≤ k + m := obtain (l : ℕ) (Hl : n + l = m), from le.elim H, le.intro (calc k + n + l = k + (n + l) : add.assoc ... = k + m : by subst m) theorem add_le_add_right {n m : ℕ} (H : n ≤ m) (k : ℕ) : n + k ≤ m + k := !add.comm ▸ !add.comm ▸ add_le_add_left H k theorem le_of_add_le_add_left {k n m : ℕ} (H : k + n ≤ k + m) : n ≤ m := obtain (l : ℕ) (Hl : k + n + l = k + m), from (le.elim H), le.intro (add.cancel_left (calc k + (n + l) = k + n + l : add.assoc ... = k + m : Hl)) theorem lt_of_add_lt_add_left {k n m : ℕ} (H : k + n < k + m) : n < m := let H' := le_of_lt H in lt_of_le_and_ne (le_of_add_le_add_left H') (assume Heq, !lt.irrefl (Heq ▸ H)) theorem add_lt_add_left {n m : ℕ} (H : n < m) (k : ℕ) : k + n < k + m := lt_of_succ_le (!add_succ ▸ add_le_add_left (succ_le_of_lt H) k) theorem add_lt_add_right {n m : ℕ} (H : n < m) (k : ℕ) : n + k < m + k := !add.comm ▸ !add.comm ▸ add_lt_add_left H k theorem lt_add_of_pos_right {n k : ℕ} (H : k > 0) : n < n + k := !add_zero ▸ add_lt_add_left H n /- multiplication -/ theorem mul_le_mul_left {n m : ℕ} (k : ℕ) (H : n ≤ m) : k * n ≤ k * m := obtain (l : ℕ) (Hl : n + l = m), from le.elim H, have k * n + k * l = k * m, by rewrite [-mul.left_distrib, Hl], le.intro this theorem mul_le_mul_right {n m : ℕ} (k : ℕ) (H : n ≤ m) : n * k ≤ m * k := !mul.comm ▸ !mul.comm ▸ !mul_le_mul_left H theorem mul_le_mul {n m k l : ℕ} (H1 : n ≤ k) (H2 : m ≤ l) : n * m ≤ k * l := le.trans (!mul_le_mul_right H1) (!mul_le_mul_left H2) theorem mul_lt_mul_of_pos_left {n m k : ℕ} (H : n < m) (Hk : k > 0) : k * n < k * m := calc k * n < k * n + k : lt_add_of_pos_right Hk ... ≤ k * m : !mul_succ ▸ mul_le_mul_left k (succ_le_of_lt H) theorem mul_lt_mul_of_pos_right {n m k : ℕ} (H : n < m) (Hk : k > 0) : n * k < m * k := !mul.comm ▸ !mul.comm ▸ mul_lt_mul_of_pos_left H Hk /- min and max -/ -- Because these are defined in init/nat.lean, we cannot use the definitions in algebra. definition max (a b : ℕ) : ℕ := if a < b then b else a definition min (a b : ℕ) : ℕ := if a < b then a else b theorem max_self [simp] (a : ℕ) : max a a = a := eq.rec_on !if_t_t rfl theorem max_le {n m k : ℕ} (H₁ : n ≤ k) (H₂ : m ≤ k) : max n m ≤ k := decidable.by_cases (suppose n < m, by rewrite [↑max, if_pos this]; apply H₂) (suppose ¬ n < m, by rewrite [↑max, if_neg this]; apply H₁) theorem min_le_left (n m : ℕ) : min n m ≤ n := decidable.by_cases (suppose n < m, by rewrite [↑min, if_pos this]) (suppose ¬ n < m, assert m ≤ n, from or_resolve_right !lt_or_ge this, by rewrite [↑min, if_neg `¬ n < m`]; apply this) theorem min_le_right (n m : ℕ) : min n m ≤ m := decidable.by_cases (suppose n < m, by rewrite [↑min, if_pos this]; apply le_of_lt this) (suppose ¬ n < m, by rewrite [↑min, if_neg `¬ n < m`]) theorem le_min {n m k : ℕ} (H₁ : k ≤ n) (H₂ : k ≤ m) : k ≤ min n m := decidable.by_cases (suppose n < m, by rewrite [↑min, if_pos this]; apply H₁) (suppose ¬ n < m, by rewrite [↑min, if_neg this]; apply H₂) theorem eq_max_right {a b : ℕ} (H : a < b) : b = max a b := (if_pos H)⁻¹ theorem eq_max_left {a b : ℕ} (H : ¬ a < b) : a = max a b := (if_neg H)⁻¹ open decidable theorem le_max_right (a b : ℕ) : b ≤ max a b := by_cases (suppose a < b, eq.rec_on (eq_max_right this) !le.refl) (suppose ¬ a < b, or.rec_on (eq_or_lt_of_not_lt this) (suppose a = b, eq.rec_on this (eq.rec_on (eq.symm (max_self a)) !le.refl)) (suppose b < a, have h : a = max a b, from eq_max_left (lt.asymm this), eq.rec_on h (le_of_lt this))) theorem le_max_left (a b : ℕ) : a ≤ max a b := by_cases (suppose a < b, le_of_lt (eq.rec_on (eq_max_right this) this)) (suppose ¬ a < b, eq.rec_on (eq_max_left this) !le.refl) /- nat is an instance of a linearly ordered semiring and a lattice-/ section migrate_algebra open [classes] algebra local attribute nat.comm_semiring [instance] protected definition linear_ordered_semiring [reducible] : algebra.linear_ordered_semiring nat := ⦃ algebra.linear_ordered_semiring, nat.comm_semiring, add_left_cancel := @add.cancel_left, add_right_cancel := @add.cancel_right, lt := lt, le := le, le_refl := le.refl, le_trans := @le.trans, le_antisymm := @le.antisymm, le_total := @le.total, le_iff_lt_or_eq := @le_iff_lt_or_eq, le_of_lt := @le_of_lt, lt_irrefl := @lt.irrefl, lt_of_lt_of_le := @lt_of_lt_of_le, lt_of_le_of_lt := @lt_of_le_of_lt, lt_of_add_lt_add_left := @lt_of_add_lt_add_left, add_lt_add_left := @add_lt_add_left, add_le_add_left := @add_le_add_left, le_of_add_le_add_left := @le_of_add_le_add_left, zero_lt_one := zero_lt_succ 0, mul_le_mul_of_nonneg_left := (take a b c H1 H2, mul_le_mul_left c H1), mul_le_mul_of_nonneg_right := (take a b c H1 H2, mul_le_mul_right c H1), mul_lt_mul_of_pos_left := @mul_lt_mul_of_pos_left, mul_lt_mul_of_pos_right := @mul_lt_mul_of_pos_right ⦄ protected definition lattice [reducible] : algebra.lattice nat := ⦃ algebra.lattice, nat.linear_ordered_semiring, min := min, max := max, min_le_left := min_le_left, min_le_right := min_le_right, le_min := @le_min, le_max_left := le_max_left, le_max_right := le_max_right, max_le := @max_le ⦄ local attribute nat.linear_ordered_semiring [instance] local attribute nat.lattice [instance] migrate from algebra with nat replacing dvd → dvd, has_le.ge → ge, has_lt.gt → gt, min → min, max → max hiding add_pos_of_pos_of_nonneg, add_pos_of_nonneg_of_pos, add_eq_zero_iff_eq_zero_and_eq_zero_of_nonneg_of_nonneg, le_add_of_nonneg_of_le, le_add_of_le_of_nonneg, lt_add_of_nonneg_of_lt, lt_add_of_lt_of_nonneg, lt_of_mul_lt_mul_left, lt_of_mul_lt_mul_right, pos_of_mul_pos_left, pos_of_mul_pos_right, mul_lt_mul attribute le.trans ge.trans lt.trans gt.trans [trans] attribute lt_of_lt_of_le lt_of_le_of_lt gt_of_gt_of_ge gt_of_ge_of_gt [trans] theorem add_pos_left : ∀{a : ℕ}, 0 < a → ∀b : ℕ, 0 < a + b := take a H b, @algebra.add_pos_of_pos_of_nonneg _ _ a b H !zero_le theorem add_pos_right : ∀{a : ℕ}, 0 < a → ∀b : ℕ, 0 < b + a := take a H b, !add.comm ▸ add_pos_left H b theorem add_eq_zero_iff_eq_zero_and_eq_zero : ∀{a b : ℕ}, a + b = 0 ↔ a = 0 ∧ b = 0 := take a b : ℕ, @algebra.add_eq_zero_iff_eq_zero_and_eq_zero_of_nonneg_of_nonneg _ _ a b !zero_le !zero_le theorem le_add_of_le_left : ∀{a b c : ℕ}, b ≤ c → b ≤ a + c := take a b c H, @algebra.le_add_of_nonneg_of_le _ _ a b c !zero_le H theorem le_add_of_le_right : ∀{a b c : ℕ}, b ≤ c → b ≤ c + a := take a b c H, @algebra.le_add_of_le_of_nonneg _ _ a b c H !zero_le theorem lt_add_of_lt_left : ∀{b c : ℕ}, b < c → ∀a, b < a + c := take b c H a, @algebra.lt_add_of_nonneg_of_lt _ _ a b c !zero_le H theorem lt_add_of_lt_right : ∀{b c : ℕ}, b < c → ∀a, b < c + a := take b c H a, @algebra.lt_add_of_lt_of_nonneg _ _ a b c H !zero_le theorem lt_of_mul_lt_mul_left : ∀{a b c : ℕ}, c * a < c * b → a < b := take a b c H, @algebra.lt_of_mul_lt_mul_left _ _ a b c H !zero_le theorem lt_of_mul_lt_mul_right : ∀{a b c : ℕ}, a * c < b * c → a < b := take a b c H, @algebra.lt_of_mul_lt_mul_right _ _ a b c H !zero_le theorem pos_of_mul_pos_left : ∀{a b : ℕ}, 0 < a * b → 0 < b := take a b H, @algebra.pos_of_mul_pos_left _ _ a b H !zero_le theorem pos_of_mul_pos_right : ∀{a b : ℕ}, 0 < a * b → 0 < a := take a b H, @algebra.pos_of_mul_pos_right _ _ a b H !zero_le end migrate_algebra theorem zero_le_one : 0 ≤ 1 := dec_trivial /- properties specific to nat -/ theorem lt_intro {n m k : ℕ} (H : succ n + k = m) : n < m := lt_of_succ_le (le.intro H) theorem lt_elim {n m : ℕ} (H : n < m) : ∃k, succ n + k = m := le.elim (succ_le_of_lt H) theorem lt_add_succ (n m : ℕ) : n < n + succ m := lt_intro !succ_add_eq_succ_add theorem eq_zero_of_le_zero {n : ℕ} (H : n ≤ 0) : n = 0 := obtain (k : ℕ) (Hk : n + k = 0), from le.elim H, eq_zero_of_add_eq_zero_right Hk /- succ and pred -/ theorem le_of_lt_succ {m n : nat} (H : m < succ n) : m ≤ n := le_of_succ_le_succ H theorem lt_iff_succ_le (m n : nat) : m < n ↔ succ m ≤ n := iff.rfl theorem lt_succ_iff_le (m n : nat) : m < succ n ↔ m ≤ n := iff.intro le_of_lt_succ lt_succ_of_le theorem self_le_succ (n : ℕ) : n ≤ succ n := le.intro !add_one theorem succ_le_or_eq_of_le {n m : ℕ} (H : n ≤ m) : succ n ≤ m ∨ n = m := or.elim (lt_or_eq_of_le H) (suppose n < m, or.inl (succ_le_of_lt this)) (suppose n = m, or.inr this) theorem pred_le_of_le_succ {n m : ℕ} : n ≤ succ m → pred n ≤ m := nat.cases_on n (assume H, !pred_zero⁻¹ ▸ zero_le m) (take n', suppose succ n' ≤ succ m, have n' ≤ m, from le_of_succ_le_succ this, !pred_succ⁻¹ ▸ this) theorem succ_le_of_le_pred {n m : ℕ} : succ n ≤ m → n ≤ pred m := nat.cases_on m (assume H, absurd H !not_succ_le_zero) (take m', suppose succ n ≤ succ m', have n ≤ m', from le_of_succ_le_succ this, !pred_succ⁻¹ ▸ this) theorem pred_le_pred_of_le {n m : ℕ} : n ≤ m → pred n ≤ pred m := nat.cases_on n (assume H, pred_zero⁻¹ ▸ zero_le (pred m)) (take n', suppose succ n' ≤ m, !pred_succ⁻¹ ▸ succ_le_of_le_pred this) theorem pre_lt_of_lt : ∀ {n m : ℕ}, n < m → pred n < m | 0 m h := h | (succ n) m h := lt_of_succ_lt h theorem lt_of_pred_lt_pred {n m : ℕ} (H : pred n < pred m) : n < m := lt_of_not_ge (suppose m ≤ n, not_lt_of_ge (pred_le_pred_of_le this) H) theorem le_or_eq_succ_of_le_succ {n m : ℕ} (H : n ≤ succ m) : n ≤ m ∨ n = succ m := or_of_or_of_imp_left (succ_le_or_eq_of_le H) (suppose succ n ≤ succ m, show n ≤ m, from le_of_succ_le_succ this) theorem le_pred_self (n : ℕ) : pred n ≤ n := nat.cases_on n (pred_zero⁻¹ ▸ !le.refl) (take k : ℕ, (!pred_succ)⁻¹ ▸ !self_le_succ) theorem succ_pos (n : ℕ) : 0 < succ n := !zero_lt_succ theorem succ_pred_of_pos {n : ℕ} (H : n > 0) : succ (pred n) = n := (or_resolve_right (eq_zero_or_eq_succ_pred n) (ne.symm (ne_of_lt H)))⁻¹ theorem exists_eq_succ_of_lt {n m : ℕ} (H : n < m) : exists k, m = succ k := discriminate (suppose m = 0, absurd (this ▸ H) !not_lt_zero) (take l, suppose m = succ l, exists.intro l this) theorem lt_succ_self (n : ℕ) : n < succ n := lt.base n lemma lt_succ_of_lt {i j : nat} : i < j → i < succ j := assume Plt, lt.trans Plt (self_lt_succ j) /- other forms of induction -/ protected definition strong_rec_on {P : nat → Type} (n : ℕ) (H : ∀n, (∀m, m < n → P m) → P n) : P n := have ∀ {n m : nat}, m < n → P m, from take n, nat.rec_on n (show ∀m, m < 0 → P m, from take m H, absurd H !not_lt_zero) (take n', assume IH : ∀ {m : nat}, m < n' → P m, assert P n', from H n' @IH, show ∀m, m < succ n' → P m, from take m, suppose m < succ n', or.by_cases (lt_or_eq_of_le (le_of_lt_succ this)) (suppose m < n', IH this) (suppose m = n', by subst m; assumption)), this !lt_succ_self protected theorem strong_induction_on {P : nat → Prop} (n : ℕ) (H : ∀n, (∀m, m < n → P m) → P n) : P n := nat.strong_rec_on n H protected theorem case_strong_induction_on {P : nat → Prop} (a : nat) (H0 : P 0) (Hind : ∀(n : nat), (∀m, m ≤ n → P m) → P (succ n)) : P a := nat.strong_induction_on a (take n, show (∀ m, m < n → P m) → P n, from nat.cases_on n (suppose (∀ m, m < 0 → P m), show P 0, from H0) (take n, suppose (∀ m, m < succ n → P m), show P (succ n), from Hind n (take m, assume H1 : m ≤ n, this _ (lt_succ_of_le H1)))) /- pos -/ theorem by_cases_zero_pos {P : ℕ → Prop} (y : ℕ) (H0 : P 0) (H1 : ∀ {y : nat}, y > 0 → P y) : P y := nat.cases_on y H0 (take y, H1 !succ_pos) theorem eq_zero_or_pos (n : ℕ) : n = 0 ∨ n > 0 := or_of_or_of_imp_left (or.swap (lt_or_eq_of_le !zero_le)) (suppose 0 = n, by subst n) theorem pos_of_ne_zero {n : ℕ} (H : n ≠ 0) : n > 0 := or.elim !eq_zero_or_pos (take H2 : n = 0, by contradiction) (take H2 : n > 0, H2) theorem ne_zero_of_pos {n : ℕ} (H : n > 0) : n ≠ 0 := ne.symm (ne_of_lt H) theorem exists_eq_succ_of_pos {n : ℕ} (H : n > 0) : exists l, n = succ l := exists_eq_succ_of_lt H theorem pos_of_dvd_of_pos {m n : ℕ} (H1 : m ∣ n) (H2 : n > 0) : m > 0 := pos_of_ne_zero (suppose m = 0, assert n = 0, from eq_zero_of_zero_dvd (this ▸ H1), ne_of_lt H2 (by subst n)) /- multiplication -/ theorem mul_lt_mul_of_le_of_lt {n m k l : ℕ} (Hk : k > 0) (H1 : n ≤ k) (H2 : m < l) : n * m < k * l := lt_of_le_of_lt (mul_le_mul_right m H1) (mul_lt_mul_of_pos_left H2 Hk) theorem mul_lt_mul_of_lt_of_le {n m k l : ℕ} (Hl : l > 0) (H1 : n < k) (H2 : m ≤ l) : n * m < k * l := lt_of_le_of_lt (mul_le_mul_left n H2) (mul_lt_mul_of_pos_right H1 Hl) theorem mul_lt_mul_of_le_of_le {n m k l : ℕ} (H1 : n < k) (H2 : m < l) : n * m < k * l := have H3 : n * m ≤ k * m, from mul_le_mul_right m (le_of_lt H1), have H4 : k * m < k * l, from mul_lt_mul_of_pos_left H2 (lt_of_le_of_lt !zero_le H1), lt_of_le_of_lt H3 H4 theorem eq_of_mul_eq_mul_left {m k n : ℕ} (Hn : n > 0) (H : n * m = n * k) : m = k := have n * m ≤ n * k, by rewrite H, have m ≤ k, from le_of_mul_le_mul_left this Hn, have n * k ≤ n * m, by rewrite H, have k ≤ m, from le_of_mul_le_mul_left this Hn, le.antisymm `m ≤ k` this theorem eq_of_mul_eq_mul_right {n m k : ℕ} (Hm : m > 0) (H : n * m = k * m) : n = k := eq_of_mul_eq_mul_left Hm (!mul.comm ▸ !mul.comm ▸ H) theorem eq_zero_or_eq_of_mul_eq_mul_left {n m k : ℕ} (H : n * m = n * k) : n = 0 ∨ m = k := or_of_or_of_imp_right !eq_zero_or_pos (assume Hn : n > 0, eq_of_mul_eq_mul_left Hn H) theorem eq_zero_or_eq_of_mul_eq_mul_right {n m k : ℕ} (H : n * m = k * m) : m = 0 ∨ n = k := eq_zero_or_eq_of_mul_eq_mul_left (!mul.comm ▸ !mul.comm ▸ H) theorem eq_one_of_mul_eq_one_right {n m : ℕ} (H : n * m = 1) : n = 1 := have H2 : n * m > 0, by rewrite H; apply succ_pos, or.elim (le_or_gt n 1) (suppose n ≤ 1, have n > 0, from pos_of_mul_pos_right H2, show n = 1, from le.antisymm `n ≤ 1` (succ_le_of_lt this)) (suppose n > 1, have m > 0, from pos_of_mul_pos_left H2, have n * m ≥ 2 * 1, from mul_le_mul (succ_le_of_lt `n > 1`) (succ_le_of_lt this), have 1 ≥ 2, from !mul_one ▸ H ▸ this, absurd !lt_succ_self (not_lt_of_ge this)) theorem eq_one_of_mul_eq_one_left {n m : ℕ} (H : n * m = 1) : m = 1 := eq_one_of_mul_eq_one_right (!mul.comm ▸ H) theorem eq_one_of_mul_eq_self_left {n m : ℕ} (Hpos : n > 0) (H : m * n = n) : m = 1 := eq_of_mul_eq_mul_right Hpos (H ⬝ !one_mul⁻¹) theorem eq_one_of_mul_eq_self_right {n m : ℕ} (Hpos : m > 0) (H : m * n = m) : n = 1 := eq_one_of_mul_eq_self_left Hpos (!mul.comm ▸ H) theorem eq_one_of_dvd_one {n : ℕ} (H : n ∣ 1) : n = 1 := dvd.elim H (take m, suppose 1 = n * m, eq_one_of_mul_eq_one_right this⁻¹) /- min and max -/ open decidable theorem le_max_left_iff_true [simp] (a b : ℕ) : a ≤ max a b ↔ true := iff_true_intro (le_max_left a b) theorem le_max_right_iff_true [simp] (a b : ℕ) : b ≤ max a b ↔ true := iff_true_intro (le_max_right a b) theorem min_zero [simp] (a : ℕ) : min a 0 = 0 := by rewrite [min_eq_right !zero_le] theorem zero_min [simp] (a : ℕ) : min 0 a = 0 := by rewrite [min_eq_left !zero_le] theorem max_zero [simp] (a : ℕ) : max a 0 = a := by rewrite [max_eq_left !zero_le] theorem zero_max [simp] (a : ℕ) : max 0 a = a := by rewrite [max_eq_right !zero_le] theorem min_succ_succ [simp] (a b : ℕ) : min (succ a) (succ b) = succ (min a b) := by_cases (suppose a < b, by unfold min; rewrite [if_pos this, if_pos (succ_lt_succ this)]) (suppose ¬ a < b, assert h : ¬ succ a < succ b, from assume h, absurd (lt_of_succ_lt_succ h) this, by unfold min; rewrite [if_neg this, if_neg h]) theorem max_succ_succ [simp] (a b : ℕ) : max (succ a) (succ b) = succ (max a b) := by_cases (suppose a < b, by unfold max; rewrite [if_pos this, if_pos (succ_lt_succ this)]) (suppose ¬ a < b, assert ¬ succ a < succ b, from assume h, absurd (lt_of_succ_lt_succ h) this, by unfold max; rewrite [if_neg `¬ a < b`, if_neg `¬ succ a < succ b`]) theorem lt_min {a b c : ℕ} (H₁ : a < b) (H₂ : a < c) : a < min b c := decidable.by_cases (suppose b ≤ c, by rewrite (min_eq_left this); apply H₁) (suppose ¬ b ≤ c, assert c ≤ b, from le_of_lt (lt_of_not_ge this), by rewrite (min_eq_right this); apply H₂) theorem max_lt {a b c : ℕ} (H₁ : a < c) (H₂ : b < c) : max a b < c := decidable.by_cases (suppose a ≤ b, by rewrite (max_eq_right this); apply H₂) (suppose ¬ a ≤ b, assert b ≤ a, from le_of_lt (lt_of_not_ge this), by rewrite (max_eq_left this); apply H₁) theorem min_add_add_left (a b c : ℕ) : min (a + b) (a + c) = a + min b c := decidable.by_cases (suppose b ≤ c, assert a + b ≤ a + c, from add_le_add_left this _, by rewrite [min_eq_left `b ≤ c`, min_eq_left this]) (suppose ¬ b ≤ c, assert c ≤ b, from le_of_lt (lt_of_not_ge this), assert a + c ≤ a + b, from add_le_add_left this _, by rewrite [min_eq_right `c ≤ b`, min_eq_right this]) theorem min_add_add_right (a b c : ℕ) : min (a + c) (b + c) = min a b + c := by rewrite [add.comm a c, add.comm b c, add.comm _ c]; apply min_add_add_left theorem max_add_add_left (a b c : ℕ) : max (a + b) (a + c) = a + max b c := decidable.by_cases (suppose b ≤ c, assert a + b ≤ a + c, from add_le_add_left this _, by rewrite [max_eq_right `b ≤ c`, max_eq_right this]) (suppose ¬ b ≤ c, assert c ≤ b, from le_of_lt (lt_of_not_ge this), assert a + c ≤ a + b, from add_le_add_left this _, by rewrite [max_eq_left `c ≤ b`, max_eq_left this]) theorem max_add_add_right (a b c : ℕ) : max (a + c) (b + c) = max a b + c := by rewrite [add.comm a c, add.comm b c, add.comm _ c]; apply max_add_add_left theorem max_eq_right' {a b : ℕ} (H : a < b) : max a b = b := if_pos H -- different versions will be defined in algebra theorem max_eq_left' {a b : ℕ} (H : ¬ a < b) : max a b = a := if_neg H /- greatest -/ section greatest variable (P : ℕ → Prop) variable [decP : ∀ n, decidable (P n)] include decP -- returns the largest i < n satisfying P, or n if there is none. definition greatest : ℕ → ℕ | 0 := 0 | (succ n) := if P n then n else greatest n theorem greatest_of_lt {i n : ℕ} (ltin : i < n) (Hi : P i) : P (greatest P n) := begin induction n with [m, ih], {exact absurd ltin !not_lt_zero}, {cases (decidable.em (P m)) with [Psm, Pnsm], {rewrite [↑greatest, if_pos Psm]; exact Psm}, {rewrite [↑greatest, if_neg Pnsm], have neim : i ≠ m, from assume H : i = m, absurd (H ▸ Hi) Pnsm, have ltim : i < m, from lt_of_le_of_ne (le_of_lt_succ ltin) neim, apply ih ltim}} end theorem le_greatest_of_lt {i n : ℕ} (ltin : i < n) (Hi : P i) : i ≤ greatest P n := begin induction n with [m, ih], {exact absurd ltin !not_lt_zero}, {cases (decidable.em (P m)) with [Psm, Pnsm], {rewrite [↑greatest, if_pos Psm], apply le_of_lt_succ ltin}, {rewrite [↑greatest, if_neg Pnsm], have neim : i ≠ m, from assume H : i = m, absurd (H ▸ Hi) Pnsm, have ltim : i < m, from lt_of_le_of_ne (le_of_lt_succ ltin) neim, apply ih ltim}} end end greatest end nat